ANALYSIS OF DYNAMIC TIME WARPING IN THE DEVELOPMENT OF GROSS REGIONAL DOMESTIC PRODUCT YOGYAKARTA - Inggrid Septa Narendra; Muhammad Muhajir (Jurnal Riset Informatika, 2022)
Poverty in Indonesia has become a common thing that is still difficult to handle due to the presence of the covid virus outbreak attacks are causing the inability to buy and sell transactions, export and import goods and services, then the level of inequality increases. The tool measures the inequality level in an area seen from the Gini Ratio value. The Gini Ratio notes that the DI Yogyakarta province had the highest index value in Indonesia of 0,437 in September 2020. So this study aims to minimize the inequality in the DI Yogyakarta province by using the clustering method and Dynamic Location Quotient (DLQ). The clustering method with a hierarchical algorithm using the Dynamic Time Warping (DTW) distance and the DLQ method to predict regional economic sectors. Based on the result of the clustering analysis, there were 2 clusters, and the DLQ analysis obtained as many as 11 essential and 6 NPN-base sectors. Cluster 1 has 10 GRDP sectors with two industries that will become non-base sectors in the future, while cluster 2 has 7 GRDP sectors with three sectors it will become base sectors in the future.